A Debreceni Egyetem Állam- és Jogtudományi Kar 100 éve 1914 – 2014 című kiállítás megnyitása - Szabó, Béla (Gerundium, 2015)
THE OPENING OF THE EXHIBITION „100 YEARS OF FACULTY OF LAW OF THE UNIVERSITY OF DEBRECEN”. In the fall of 2014 the Faculty of Arts and the Faculty of Law of the University of Debrecen celebrated the 100th anniversary of beginning of university training. Just as the Faculty of Arts, the Faculty of Law commemorated the anniversary with an exhibition. he published speech was presented at the opening of the exhibition organized in the the Library of Social sciences. It relects on the importance of keeping traditions and on the reassuring thoughts addressed to the teachers and students of the Faculty.